Estimated Cost of Power Losses Due to Imbalance, No-Load and On-Load on Transformers in 2023-2033 - Liliana, Liliana; Aini, Zulfatri; Bandri, Sepannur (DPTE FT UNY, 2024)
The greater the power losses, the higher the loss costs for the transformer. These losses can occur due to load, no-load, and load imbalance factors. This study aims to obtain the cost of losses incurred due to these three factors for ten years (2023-2033). The estimated cost of losses due to unbalance is obtained from the calculation of power losses in the neutral of the transformer, the cost of no-load losses is obtained from the losses of the iron core in the transformer, In contrast the cost of load losses is influenced by the development of the load and the interest rate for each year. As a result, the greatest power losses occur under unbalanced conditions with an average load for ten years of 88.68%, followed by no-load conditions of 11.10% and 0.21% load. The total power losses for ten years amounted to Rp. 3,029,196,416.64.